2010
DOI: 10.3109/08039481003710212
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Ward Atmosphere Scale in a Russian psychiatric hospital

Abstract: The revised WAS version appeared applicable within this Russian psychiatric hospital context. Several of the items that were dropped appeared inapplicable because of differences between Russian and Western culture and psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The present study has also revealed that socio-demographic characteristics and disease data of the patients were significantly different between SFS scores in three measurements and mean SFS scores of men were higher than women (Table 2). This finding is parallel with the literature [26,30,31]. Majority of the female participants were housewives.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study has also revealed that socio-demographic characteristics and disease data of the patients were significantly different between SFS scores in three measurements and mean SFS scores of men were higher than women (Table 2). This finding is parallel with the literature [26,30,31]. Majority of the female participants were housewives.…”
Section: Discussionsupporting
confidence: 90%
“…Besides this, mean SFS scores significantly differed based on patients' medical diagnosis in three repeated measurements and differences resulted from the third, which showed also that whatever the diagnosis was, the level of functionality of the patients after discharge was higher than with disease onset and during clinic admission. Relevant studies have shown that a well-structured ward atmosphere increases social functionality of patients [11,12,17,25,26]. In this respect, it seems that the relevant ward's atmosphere-despite having requirement to be improved -contributed to the development in patients' social functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous research has confirmed both the content [45] and criterion validity [46] of the WAS. Additionally, it has been implemented in several cross-cultural contexts [24,29,31,47].…”
Section: Instrumentationmentioning
confidence: 99%
“…Additionally, Jörgensen, Römma, and Rundmo (2009) [23] utilized the Ward Atmosphere Scale and discovered a correlation between the Ward Atmosphere Scale and juvenile satisfaction, while acknowledging more research was necessary. Social climate has been a concept researched in the previous decades [25, [29][30][31], and focused on the perspective within a hospital inpatient unit as opposed to correctional centers.…”
Section: Introductionmentioning
confidence: 99%